2002
DOI: 10.1042/bj20020658
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the rat type IIA phospholipase A2 gene by cAMP and interleukin-1β in vascular smooth muscle cells: interplay of the CCAAT/enhancer binding protein (C/EBP), nuclear factor-κB and Ets transcription factors

Abstract: The abundant secretion of type IIA secreted phospholipase A(2) (sPLA(2)) is a major feature of the inflammatory process of atherosclerosis. sPLA(2) is crucial for the development of inflammation, as it catalyses the production of lipid mediators and induces the proliferation of smooth muscle cells. We have analysed the activation of sPLA(2) transcription by cAMP and interleukin-1beta (IL-1beta), and shown that the 500 bp region upstream of the transcription start site of the rat sPLA(2) gene is implicated in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 37 publications
(53 reference statements)
1
57
0
Order By: Relevance
“…[Ϫ488;ϩ46] sPLA2-luc and mutant constructs were obtained by site-directed mutagenesis as previously described. 23 …”
Section: Plasmid Constructsmentioning
confidence: 99%
See 3 more Smart Citations
“…[Ϫ488;ϩ46] sPLA2-luc and mutant constructs were obtained by site-directed mutagenesis as previously described. 23 …”
Section: Plasmid Constructsmentioning
confidence: 99%
“…We have previously shown that the best characterized activators of gene expression during inflammation, the nuclear factor-B (NF-B), CAAT/enhancer-binding protein (C/EBP), and winged helix-turn-helix transcription factors (Ets-1), are involved in the stimulation of rat sPLA2-IIA gene transcription by IL-1␤ and cAMP. 23 Therefore, we investigated whether these transcription factors were involved in the induction of the sPLA2-IIA transcription by the hsPLA2-IIA supernatant using [-488;ϩ46] luc constructs mutated for the transcription factor binding sites. The luciferase/␤-galactosidase activity ratio stimulation obtained with the hsPLA2-IIA supernatant was abolished with the mutant constructs, whereas forskolin still induced the transcription of the mutant Ets and mutant NF-kB constructs (Figure 4).…”
Section: Amandine Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…I). Sp1 is a transcription factor known to regulate the activities of proteins involved in eicosanoid production, such as cPLA 2 [55], sPLA 2 [56], platelet-activating factor acetylhydrolase (PAF-AH) [57], and 12(S)-lipoxygenase [58].…”
Section: A Sp1-binding Stimulatory Element and An Inhibitory Element mentioning
confidence: 99%